Selection of Inventory Valuation Method Using FIFO and Weighted Averaged - Aulia Azahra; Rahmat Siauwijaya (Bina Nusantara University, 2022)
The research aims to analyze the factors that influence the selection of inventory valuation methods. This study employs case questions and SPSS version 24 to answer the research questions. Seventy-three manufacturing firms listed in the Indonesian stock exchange from 2010-2019 were selected with the purposive sampling method and analyzed with binary logistic regression. The results reveal that the selection of inventory valuation method affected taxes, net income, and ending inventory. Moreover, it is found that Inventory turnover and gross profit margin significantly affect inventory valuation selection methods. In contrast, current ratio and financial leverage do not significantly affect inventory valuation selection methods.